Salient features of mesenchymal stem cells—implications for Ewing sarcoma modeling - Monument, Michael J.; Bernthal, Nicholas; Randall, R. Lor (Frontiers in Oncology, 2013)
Despite a heightened appreciation of the many defining molecular aberrations in Ewing sarcoma, the cooperative genetic environment and permissive cell of origin essential for EWS/ETS-mediated oncogenesis remain elusive. Consequently, inducible animal and in vitro models of Ewing sarcoma from a native cellular context are unable to fully recapitulate malignant transformation. Despite these shortcomings, human and murine mesenchymal stem cells (MSCs) are the closest working in vitro systems available: MSCs are tolerant of ectopic EWS/FLI expression, which is accompanied by a molecular signature most similar to Ewing sarcoma. Whether MSCs are the elusive cell of origin or simply a tolerant platform of the EWS/FLI transcriptome, these cells have become an excellent molecular tool to investigate and manipulate oncogenesis in Ewing sarcoma. Our understanding of the biological complexity and heterogeneity of human MSCs has increased substantially over time and as such, appreciation and utilization of these salient complexities may greatly enhance the efficient use of these cells as surrogate models for Ewing sarcoma tumorigenesis.